Repositioning the Theory of Dialectical Translation of Religious Texts in Qur'anic Perspective - Nuroh, Nuroh; Rohmatul Uyuni , Yuyun (Al Qalam, 2023)
Dialectics focuses on understanding the context of the al-Qur'an and is integrated as a method of dialogue between the original text and the translation. By developing a new framework that combines al-Qur’an dialectics and religious values through textual analysis and literature review. This study provides a critical review of translation theory, investigating the relationship between language and religious meaning in the al-Qur'an text. The combination of dialectical aspects and al-Qur'an perspectives is expected to make a significant contribution to the development of theories on the translation of religious texts, especially in the Islamic context. The practical implications include the development of more contextualized and detailed translation guidelines as well as a more comprehensive understanding of the religious meaning embedded in the al-Qur'an text. The methodology used is library research using a descriptive qualitative approach and book research involving textual analysis of religious texts in the al-Qur'an, followed by a literature review of existing translation theories. The results of this analysis form the basis for the development of a dialectical model in the translation of religious texts, in which cultural, historical and linguistic contexts become key considerations. By utilizing the al-Qur'an perspective, this research directs the translation of religious texts towards a deeper and more contextual understanding.